A crosstalk between circular RNA, microRNA, and messenger RNA in the development of various brain cognitive disorders - He, Liang; Zhang, Furong; Zhu, Yuling; Lu, Meilin (Frontiers in Molecular Neuroscience, 2022)
Patients suffering from Alzheimer’s disease (AD), Parkinson’s disease (PD), traumatic brain injury (TBI), stroke, and postoperative neurocognitive disorder (POND) are commonly confronted with neurocognitive disorders with limitations in available therapeutics. Some noncoding RNAs (ncRNAs) are involved in the development of various brain cognitive disorders. The circular RNAs (circRNAs), a typical group of ncRNAs, can function as competing endogenous RNAs (ceRNAs) to mainly deplete the microRNA (miRNA) downregulation of targeted messenger RNAs (mRNAs). The circRNAs are abundant in central nervous system (CNS) diseases and contribute to brain disorders, but the exact roles of circRNAs have not been clear. The crosstalk of circRNA, miRNA and mRNA act as important roles in the pathogenesis of these neurocognitive dysfunction diseases and abnormal l conditions including AD, PD, stroke, TBI, and POND. In this review, we summarized the circRNA participate in neuroglia damage and inflammation. At last, we aimed to highlight on the regulatory mechanisms of circRNA-miRNA-mRNA networks in the development of various brain cognitive disorders and provide new insights into therapeutics on these diseases.